Effect of Specific Tactical Exercises in Some Biochemical Indicators and Psychological Endurance and Achievement of 400 M Hurdles for Young Players - Mahmoud Nasser Radi1, Ali Bukheet Hassan1, Muntadher Mohammed Ali1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study dealt with several topics including the introduction of the research and the importance of the use of specialized tactical training during the training units, which are manifested in the development of biochemical indicators, psychological tolerance and performance of the effectiveness of 400 m hurdles, so researchers thought to conduct this study and go in the process to identify the results that will be achieved. In the results to the lack of the use of specialized lactic exercises, which are based on scientific foundations and that would make adaptations functional, in addition to the effectiveness of this need of self-sufficiency of large runners because it is a difficult activity that requires the will and determination to win, if The research problem involves two main axes: the first is the low speed restriction and tolerance of the special speed in the 400 m hurdles, and the second axis in the search is to obtain a high level of functional efficiency of some biochemical indicators associated with special speed and the tolerance of the speed Therefore, the researchers considered going into this experiment.